Botulism in the Pediatric Intensive Care Units in the United States: Interrogating a National Database - Howes, Cynthia; Hiatt, Kerith; Turlington, Katherine; Foster, Cortney; Holloway, Adrian; Graciano, Ana Lia; Custer, Jason; Bhutta, Adnan; Bagdure, Dayanand (Journal of Pediatric Intensive Care, 2020)
Botulism in children can have severe complications necessitating intensive care. The current literature lacks data of children with botulism requiring critical care. We aim to describe the outcomes of pediatric botulism in the pediatric intensive care unit (PICU). Retrospective cohort data from Virtual Pediatric Systems (VPS, LLC, Los Angeles, California), from 2009 to 2016 including all PICU admissions among children with botulism, were analyzed. Characteristics and outcomes were compared with similar studies. A total of 380 children were identified over 8 years. Our cohort had the shortest length of stay (median 4.6 days), the smallest percent requiring mechanical ventilation (40%), and the highest median age (120 days) amongst comparable studies. Length of mechanical ventilation and PICU stay has decreased among children with botulism. Advances in PICU care may have contributed to these improved outcomes.
Keywords: botulism; pediatrics; pediatric intensive care unit; mechanical ventilation